PERBEDAAN TINGKAT PERKEMBANGAN BAYI YANG DIBERI ASI EKSKLUSIF DAN NON EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PADANG KARAMBIA KECAMATAN PAYAKUMBUH SELATAN - Nur Sakinah; Ni Luh Nopi Andayani; I Made Krisna Dinata (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACTDevelopment refers to change or growth that occurs in a child during the life span from birth to adolescence. Thischange occurs in an orderly sequence, involving, physical, cognitive, and emotional development. The research wasaimed to determine the effect of breastfeeding differences on the grade of infant development. The research wasalso aimed to prove the different grade of development of infants given exclusive breastfeeding and non exclusive.This research is analytics observational with cross sectional approach and total sampling as sampling technique.Development were seen using a pre-screening developmental questionnaire (KPSP) with charging directly by respondentsaccompanied by researchers. The results of a questionnaire be consider to be normal, suspect and delayinterpretation. The result of research among 30 people (19 people each of exclusive breastfeeding and 21 people fornon exclusive breastfeeding) showed that there is no difference in the development of breastfed infants exclusive andnon exclusive using chi-square test with the result p=1 or p > 0,05.Keywords: Development, Breast Feeding